Demographic transition and socio-economic development in Malaysia - Tey, Nai Peng; Lai, Siow Li; Noor Azina Ismail (University of Malaya Press, 2020)
In Malaysia, the demographic transition of mortality and fertility from a high to a low level has resulted in a dramatic age structural shift, giving rise to a demographic dividend. Malaysia has put in place the various mechanisms in development planning to improve human capital. Consequently, Malaysia has done well to realize the demographic dividend in achieving rapid socio economic development, which in turn a